2014
DOI: 10.1371/journal.pone.0105607
|View full text |Cite
|
Sign up to set email alerts
|

Daily Liquorice Consumption for Two Weeks Increases Augmentation Index and Central Systolic and Diastolic Blood Pressure

Abstract: BackgroundLiquorice ingestion often elevates blood pressure, but the detailed haemodynamic alterations are unknown. We studied haemodynamic changes induced by liquorice consumption in 20 subjects versus 30 controls with average blood pressures of 120/68 and 116/64 mmHg, respectively.MethodsHaemodynamic variables were measured in supine position before and after two weeks of liquorice consumption (daily glycyrrhizin dose 290–370 mg) with tonometric recording of radial blood pressure, pulse wave analysis, and wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 38 publications
(46 reference statements)
1
35
0
1
Order By: Relevance
“…Specific agents such as non‐steroidal anti‐inflammatory drugs (NSAIDs) and Kanzo [liquorice] increase the circulating volume, resulting in a non‐dipping pattern and nocturnal hypertension …”
Section: Resultsmentioning
confidence: 99%
“…Specific agents such as non‐steroidal anti‐inflammatory drugs (NSAIDs) and Kanzo [liquorice] increase the circulating volume, resulting in a non‐dipping pattern and nocturnal hypertension …”
Section: Resultsmentioning
confidence: 99%
“…Exclusion criteria were office BP >140/90 mmHg, cardiovascular disease with regular medication, pregnancy, and consumption of liquorice >300 grams per week. Subject recruitment and data collection have been described previously 8 . The liquorice group consisted of 22 subjects (14 women and 8 men), and the aged-matched control group of 30 subjects (17 women and 13 men).…”
Section: Methodsmentioning
confidence: 99%
“…We recently reported that daily liquorice consumption in normotensive subjects for two weeks elevated peripheral and central systolic and diastolic BP, increased extracellular fluid volume, and amplified pressure wave reflection from the peripheral arterial tree 8 . However, increased peripheral arterial resistance and large arterial stiffness, and changes in cardiac function and autonomic tone could also contribute to the elevation of BP following liquorice ingestion.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The USA Food and Drug Administration (FDA) advises avoiding eating large amounts of black licorice at one time [ 7 ]. An increase in extracellular volume and elevation of central systolic and diastolic blood pressure after two weeks of daily licorice consumption have been reported [ 8 ]. However, it has been suggested that individual factors may predispose to pseudoaldosteronism in certain patients, since some patients develop neither hypokalemia nor hypertension even after long time consuming licorice.…”
Section: Discussionmentioning
confidence: 99%